PENGARUH KUALITAS PELAYANAN TERPADU SATU PINTU (PTSP) TERHADAP KEPUASAN MASYARAKAT PADA PENGADILAN TINGGI AGAMA JAKARTA - Sri Yanthy Yosepha; Restiana Irwanti (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
The One Stop Integrated Service (PTSP) in court has a major influence on the services provided to the community. The community has an easier time and trust in the courts. Fast and transparent, an impression built on court. Public trust in the courts has also increased. Society is easier to obtain information. Just come to the PTSP court. Public satisfaction with the one-stop integrated service becomes a court evaluation in maintaining or improving service quality. This study aims to determine the effect of one stop service quality (PTSP) on community satisfaction at the Jakarta Religious High Court. This study uses a literature review of several previous research results in Indonesia. The results of the analysis of the effect of PTSP service quality on community satisfaction at the Jakarta High Religious Court can be concluded as follows: Service quality has a partial effect on community satisfaction of PTSP users at the Jakarta High Religious Court.